2014
DOI: 10.1093/ntr/ntu018
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Tobacco Advertising Exposure and Conduct Problems on Smoking Behaviors Among Adolescent Males and Females

Abstract: The findings of this study reinforce that conduct problems are a strong predictor of subsequent current smoking for all adolescents and reveal important differences between adolescent males and females in the relationship between conduct problems, tobacco advertising behavior, and smoking behavior. The findings suggest gender-specific preventive interventions targeting advertising exposure may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Our study evaluated college-age youth for whom e-cigarettes are a relatively novel product. These findings should also be replicated in a larger sample to test for sex/gender differences, given evidence for sex/gender differences in e-cigarette susceptibility (Bold et al, 2016), use and preferences for flavored e-cigarettes (e.g., Dawkins et al, 2013), and responsiveness to tobacco advertising (Mays et al, 2014) and health warnings (O'Hegarty et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Our study evaluated college-age youth for whom e-cigarettes are a relatively novel product. These findings should also be replicated in a larger sample to test for sex/gender differences, given evidence for sex/gender differences in e-cigarette susceptibility (Bold et al, 2016), use and preferences for flavored e-cigarettes (e.g., Dawkins et al, 2013), and responsiveness to tobacco advertising (Mays et al, 2014) and health warnings (O'Hegarty et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…A single item also measured whether participants had ever tried e-cigarettes (yes/no) [ 5 ]. Another item measured exposure to e-cigarette advertising in magazines, on television, or convenience stores based on a five point scale [ 33 , 34 ]. Four items also assessed past 30 day use of smokeless tobacco; cigars; little cigars and cigarillos; and waterpipe (hookah) tobacco use [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…Parent social status of the participants were the father and mother living together and that was also expected because the nature of the Iraqi society that the family always lives together and the dominant relationship between father and mother is the marriage status, as the high percentage of the parent status was living together, the same result with Mays et al, 2014 they found that the majority parents living status of the participants still married and living together (15) , the vast majority of the adolescents living status was the living with parents the same finding by Al-Mohamed, and Amin, 2010 study they found that the smokers participants most of them are living with their parents (16) and Gaffar et al, 2013 did find the same result (17) , such a result is normal to predict because of the nature of the Arabs countries society the whole family always still together especially when the younger members still not married they stay with the family. Fig.1 Overall assessment of study sample for overall psychological determinants The economic status of the smoking adolescents was almost equal between low status and middle status but the last one was slightly more than the other where the middle was (48.6%) while low was (45.4%) and that explains the other findings of the budget quantity per week where less or equal to ten thousand Iraqi dinars.…”
Section: Part I: Socio-demographic Data Of the Smoking Adolescentsmentioning
confidence: 78%